Monoclonal antibodies against human leucocyte antigens. II. Antibodies against CD45 (T200), CD3 (T3), CD43, CD10 (CALLA), transferrin receptor (T9), a novel broadly expressed 18-kDa antigen (MEM-43) and a novel antigen of restricted expression (MEM-74) - Horejsí, V; Angelisová, P; Bazil, V; Kristofová, H; Stoyanov, S; Stefanová, I; Hausner, P; Vosecký, M; Hilgert, I (Folia biologica, 1988)
The specificities of several monoclonal antibodies described by us earlier were determined more exactly: (1) antibodies MEM-31 and MEM-32 are directed against CD8 and CD5 T cell antigens, respectively: (2) MEM-15 and MEM-18 react with the CD14 monocyte antigen; (3) MEM-28 recognizes the CD45 pan-leucocyte antigen. Several new monoclonal antibodies are described: (4) MEM-55 and MEM-58, reactive with subsets of CD45-related molecules; (5) MEM-43, recognizing a broadly expressed 18-kDa glycoprotein; (6) MEM-57, reacting with the CD3 antigen complex: (7) MEM-59 recognizing the CD43 leucocyte antigen; (8) MEM-74, which reacts with an unidentified antigen strongly expressed on several cell lines and many leukaemic cells but absent from most resting leucocytes; (9) MEM-75, directed against transferrin receptor, and (10) MEM-78, recognizing CD10 (CALLA) antigen.
Keywords: Histocompatibility Antigens; CD3 Complex; Enzyme-Linked Immunosorbent Assay; Sialoglycoproteins; antigeny CD43; buněčné linie; histokompatibilní antigeny; antigeny CD3; CD antigeny; Antigens, Neoplasm; Leukosialin; Antibodies, Monoclonal; receptory transferinu; lidé; neprilysin; diferenciační antigeny; Receptors, Transferrin; Cell Line; leukocyty; Antigens, CD; sialoglykoproteiny; Neprilysin; ELISA; Leukocyte Common Antigens; Antigens, Differentiation; Leukocytes; Antibody Specificity; monoklonální protilátky; specificita protilátek; antigeny nádorové; antigeny CD45; Humans